Relationship of the metabolic score for insulin resistance and the risk of stroke in patients with hypertension: A cohort study - Cai, Xintian; Hu, Junli; Zhu, Qing; Wang, Mengru; Liu, Shasha; Dang, Yujie; Hong, Jing; Li, Nanfang (Frontiers in Endocrinology, 2022)
Objective: This study aimed to determine the association between the metabolic score for insulin resistance (METS-IR) and incident stroke and its subtypes within a cohort of Chinese hypertensive patients. Methods: A total of 14032 hospitalized patients with hypertension from January 1, 2010, to December 31, 2021, were included in this retrospective cohort study. Cox models and restricted cubic splines were applied to determine the association between METS-IR and the risk of stroke. Results: During a median follow-up of 4.80 years, 1067 incident stroke cases occurred. Patients in the highest quartile group of METS-IR levels exhibited a higher risk of stroke (HR, 1.80; 95% CI, 1.50-2.17) and ischemic stroke (HR, 1.96; 95% CI, 1.60–2.42) than those in the lowest quartile group. However, no significant associations were observed between METS-IR and the risk of hemorrhagic stroke. Restricted cubic spline analysis suggested a nearly J-shaped association between METS-IR and risk of stroke and ischemic stroke (P for nonlinearity < 0.001). METS-IR did produce a significant improvement in the C statistic when added to the basic model (from 0.637 to 0.664, P < 0.001). Notably, the addition of METS-IR to the basic model resulted in a significant improvement in predicting incident total stroke and ischemic stroke. Conclusions: This cohort study suggests a relationship between METS-IR and the risk of stroke and ischemic stroke. Further studies are required to elucidate the underlying mechanisms.